Fracture behavior of wood-steel dowel joints under quasi-static loading - Dourado, N. (2018)
This study analyses a common L-shape conﬁguration formed by wood members and a thick metal plate, duly fastened with steel dowels. Four connecting arrangements were experimentally tested, considering different values of space between dowels and distance to the boundary edge, which allowed measuring the initial stiffness and moment-carrying capacity. A three-dimensional ﬁnite element model, including a trapezoidal bilinear cohesive law, was developed to reproduce mixed-mode loading through cohesive zone modelling. Very satisfactory agreements between numerical predictions and experimental results were registered, regarding the full-extension of the load-displacement curves and damage proﬁles of the joints. In light of these, the model was applied in a larger range of possible combinations of distances to get global trends of the initial stiffness and moment-carrying capacity of these joints.